Entwicklung und Validierung einer neuen Methode zur Charakterisierung des Scherverhaltens von Carbonfasergewebe mit Binderauftrag unter Normalkraft und viskoser Reibung bei hohen Prozesstemperaturen - Graf, Matthias (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
In this work the influence of normal force on the shear behavior of carbon fiber fabric during the draping process at different temperatures is investigated. For this purpose an extended test method based on the picture frame test is developed and its suitability tested. The normal force and the visco-elastic friction of the binder particles applied to the fabric show a significant increase in shear resistance.